La danza nacional andina en la sarcopenia en miembros superiores en adultos mayores - Chicaiza Herrera, Alexander Ismael (2025)
This study aimed to determine the impact of Andean national dance on upper limb muscle strength in older adults with sarcopenia, emphasizing the importance of maintaining functionality and quality of life in this population. The research employed a quantitative approach and a quasi-experimental design, implementing a six-week intervention program based on Andean national dance with a purposive sample of ten older adults from the “Mark Blacklin” Geriatric Daycare Center in Riobamba. Muscle strength was evaluated using handgrip dynamometry, comparing pretest and posttest results to identify measurable changes in participants’ functional capacity. The findings revealed a significant increase in handgrip strength, suggesting that the practice of Andean dance is not only a cultural and recreational activity but also an effective, motivating, and easily applicable therapeutic strategy to mitigate the effects of sarcopenia. It is concluded that regular participation in Andean national dance enhances upper limb strength, improves functional mobility, and promotes the overall well-being of older adults. These results support the inclusion of adapted physical activity programs and geriatric rehabilitation strategies that integrate cultural and recreational elements, demonstrating that the combination of exercise, culture, and motivation contributes positively to health and quality of life in this population